National Evaluation of Racial/Ethnic Discrimination in US Surgical Residency Programs - Yuce, Tarik K. (JAMA Surg, 2020)
This cohort study surveyed resident surgeons in the US to assess their experiences of racial/ethnic discrimination in residency programs.